2017
DOI: 10.1038/s41467-017-00133-2
|View full text |Cite|
|
Sign up to set email alerts
|

Symmetry-based indicators of band topology in the 230 space groups

Abstract: The interplay between symmetry and topology leads to a rich variety of electronic topological phases, protecting states such as the topological insulators and Dirac semimetals. Previous results, like the Fu-Kane parity criterion for inversion-symmetric topological insulators, demonstrate that symmetry labels can sometimes unambiguously indicate underlying band topology. Here we develop a systematic approach to expose all such symmetry-based indicators of band topology in all the 230 space groups. This is achie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
898
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 760 publications
(926 citation statements)
references
References 48 publications
(161 reference statements)
7
898
0
Order By: Relevance
“…This local approach obfuscates any connection to band topology, which requires understanding how these different localized descriptions fit together to make a global band structure. While there has been some recent work towards addressing how symmetry constrains global band structures [14,15], a complete and constructive approach to the problem has not yet been presented.…”
mentioning
confidence: 99%
“…This local approach obfuscates any connection to band topology, which requires understanding how these different localized descriptions fit together to make a global band structure. While there has been some recent work towards addressing how symmetry constrains global band structures [14,15], a complete and constructive approach to the problem has not yet been presented.…”
mentioning
confidence: 99%
“…The authors designed what is known as the first catalog of topological electronic materials. In the same spirit, using the recently developed symmetry indicators method [363], Tanget al found 258 TIs and 165 topological crystalline insulators which have robust topological character [359], i.e., considerable full or direct band gap. The authors also found 489 topological semimetals with the band crossing points located near the Fermi level [359].…”
Section: Topological Ordered Materialsmentioning
confidence: 97%
“…As a result, the system evolves into an AFM topological (crystalline) insulator with a massive bulk Dirac cone as shown in Figure a,b. Due to the presence of a band gap in the bulk and the preserved scriptP symmetry, it is possible to calculate the topological parity‐based invariant Z 4 index, which is defined as Z4=i=18n=1nocc1+ξn(Ki)2 mod 4 33. From the calculated band structure of EuCd 2 As 2 , we obtained Z 4 = 2.…”
Section: The Number Of Occupied Bands With Even and Odd Parity At Thementioning
confidence: 99%